Аскольдовцы - Пикуль Валентин Саввич (Полное собрание сочинений, 2018)
Экземпляры: Ф. 2 (20200123) / Инвентарный номер: 47690 / Цена: 200.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: П 32 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-442